Fasting and kidney function: is it safe? - Mohsin Riaz, Muhammad; Mir, Saba; Azhar, Ayesha; Sabir, Omer; Tarif, Nauman (Pakistan Journal of Kidney Diseases, 2021)
Fasting during the month of Ramadan is a religious obligation for Muslims. This study explores the effect of fasting among patients with chronic kidney disease (CKD) with the possible risk of dehydration and diet induced hyperkalemia. Methods: Fifty (50) patients were included in this study around the month of Ramadan in 2014 .The patients were keeping their regular follow up at the Nephrology OPD. The patients were enrolled in the two weeks leading to the month of Ramadan and were followed through the Holy Month up to two weeks post Ramadan. At each visit, a thorough clinical assessment was made along with relevant lab investigations. RESULTS : 36 (72%) patients observed fasting. The mean age was 51.3 + 15.9 years. Most of the patients had CKD stage IV (45.8%), followed by stage III (25%) and stage V (16.7%). Most of the patients took fluids (80.4%) and fruits (84.3%) freely during the time between Iftar and Sehr. Half (49%) of the patients were on sodium restricted diet and one third (33.3%) were on protein restricted diet. Fasting did not significantly affect Pre and Post Ramadan office blood pressure (p= 0.676), serum creatinine (p= 0.057), serum potassium (p= 0.884), serum uric acid (p=0.607), protein to creatinine ratio (p= 0.221) or degree of edema (p= 0.149). CONCLUSIONS: It appears that fasting is reasonably safe in patients with chronic kidney disease.